QUALITY OF BPJS KESEHATAN SERVICES AT LABUANG BAJI REGIONAL GENERAL HOSPITAL, SOUTH SULAWESI - Djafar, Ismail; Ahmadi, Andi Nurhanisa; Guntur, Muhammad; Rukmana, Novayanti Sopia (Universitas Negeri Makassar, 2024)
This study aims to determine the quality of BPJS Kesehatan services at the Labuang Baji Regional General Hospital, South Sulawesi. This study is a qualitative descriptive research with a total of 6 informants. Data collection was carried out using observation, interview, and documentation techniques. The data analysis techniques used consist of data condensation, data presentation, and conclusion drawn. The results of the study show that the quality of BPJS Kesehatan services at the Labuang Baji Regional General Hospital in South Sulawesi is in the category of quite good. Looking at the focus of the research, namely: 1) physical evidence is in the inadequate category; 2) responsiveness is in the very good category; 3) reliability is in the good category; 4) the guarantee is in the poor category; and 5) empathy is in the very good category.